Essays in the economic implications of select animal health and crop production issues - Cozzens, Tyler William, author; Pendell, Dustin, advisor; Shwiff, Stephanie, committee member; Dalsted, Norman, committee member; Peel, Kraig, committee member (Colorado State University. Libraries, 2015)
Production agriculture is faced with many risks which may be difficult to manage and can result in significant negative economic impacts. For the individual farmer, this can be problematic and potentially poses a challenge to remain viable and profitable when faced with uncertain circumstances. Economic matters evaluated in this dissertation include the topics of animal health and crop production efficiency both focusing on improving production agriculture. This dissertation is comprised of three separate essays or three individual chapters. The first chapter contains an essay on a growing global threat to human health and safety and the biosecurity of livestock production in the United States in the form of antimicrobial resistant pathogens. An equilibrium displacement model (EDM) of the U.S. meat industry (i.e., beef, pork, lamb and poultry) is used to analyze welfare implications occurring from the potential restriction on the use of antimicrobial technologies or the implementation of biosecurity measures at the slaughter (i.e., feedlot) level of beef cattle production. Producer and consumer surplus measures showed that the beef industry losses the most from a reduction on the use of antimicrobial technology in beef cattle production in both the short- and long-run. An 11.95% industry adoption of a wildlife population management (WPM) program on livestock facilities cause a gain in producer surplus of $1.15 billion in the short-run with long-run gains of $18.33 million for the meat industry. The second essay assesses the impact of various biosecurity strategies to prevent the incursion of bovine viral diarrhea virus (BVDV) in a cow-calf herd and minimize the uncertain financial impacts. The specific objectives of this study are to estimate the impact of BVDV introduction to representative U.S. cow-calf operations using an epidemiological disease spread model and to estimate annual costs of BVDV in cow-calf herds. Epidemiological results will be used to evaluate the expected returns and risk for various BVDV biosecurity measures in U.S. cow-calf herds by using a linear programming model which incorporates risk. Results from the study show that, in the context of whole farm planning, vaccination, testing or a combination of both can be effective biosecurity measures to control BVDV. In all five regions, biosecurity strategy M (no biosecurity control measures) generate the highest expected returns which could be a result of no biosecurity costs. Expected returns by each biosecurity strategy shows that N (vaccination of breeding stock) generates the highest expected return for the Southern Plains (SP), North Central (NC), and West (W) regions. Biosecurity strategy T (testing for BVDV) had the highest expected returns for the Northern Plains (NP) and Southeast (SE) regions. The information from this essay is useful to the cow-calf industry as impacts and costs from various biosecurity measures are provided. The third essay estimates and analyzes efficiency measures of conventional and organic crop producers. The estimation of efficiency measures was conducted by using a non-parametric approach commonly referred to as data envelopment analysis (DEA). Estimated efficiency results were evaluated using Tobit analysis to identify those farm and producer factors that influence the efficiency of U.S. crop producers. Results indicate that on average organic producers have a higher variable returns to scale technical efficiency (0.5656) than conventional producers (0.4741) and are better at producing their maximum output level given the inputs used compared to conventional producers.